1979
DOI: 10.1093/bja/51.12.1101
|View full text |Cite
|
Sign up to set email alerts
|

Halothane Does Not Inhibit Human Neutrophil Function in Vitro

Abstract: Various indices of function of neutrophils from normal healthy volunteers have been examined after in vitro exposure to halothane. Random free movement on glass was unaffected, but random migration through millipore filters was slightly increased. There was no significant change in migration in response to casein chemotaxis. Phagocytosis, degranulation and the enhanced non-mitochondrial respiration associated with phagocytosis were unaffected. Electron-microscopic appearance at 30 s after exposure to latex par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 17 publications
2
10
1
1
Order By: Relevance
“…Similarly bactericidal activity was found to be depressed postoperatively for several days after halothane anaesthesia [21]. On the other hand, some authors have shown no effect on phagocytosis with 2% halothane [22,23]. Our results indicate that both halothane and enflurane cause a reversible depression of leucocyte function.…”
Section: Qualitative Leucocyte Functionsupporting
confidence: 63%
“…Similarly bactericidal activity was found to be depressed postoperatively for several days after halothane anaesthesia [21]. On the other hand, some authors have shown no effect on phagocytosis with 2% halothane [22,23]. Our results indicate that both halothane and enflurane cause a reversible depression of leucocyte function.…”
Section: Qualitative Leucocyte Functionsupporting
confidence: 63%
“…Enflurane has been shown to decrease phagocytosis, 8 whereas halothane, 9 isoflurane, and nitrous oxide 8 had no effect. Neutrophil and monocyte phagocytosis activity following exposure to nitrous oxide was also not affected in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Neutrophils show a naloxone-sensitive chemotactic response to endogenous opioids in a human in ritro study and a rat in t+o study [73, 741. Nunn et al showed that halothane in i 4 r o does not inhibit neutrophil ability to migrate in response to casein chemotaxis, to degrdnulate or to phagocytose beads [75]. …”
mentioning
confidence: 99%